COHESION AND HIGH PERFORMANCE SPORT: AN INDOOR SOCCER TEAM ANALYSIS. (Fiep Bulletin - online, 2014)
Cohesion is one of the elements that are determinant for a sports team performance, it is a dynamic process that reflects at the tendency of a group to unite and remain united towards their aims and goals. The objective of the present study was to investigate sport cohesion through an analysis of a professional team's group environment. Twenty subjects from a High performance indoor soccer team from the city of Maringá-PR, between athletes and coach staff, were analyzed. AS measurers instruments were used the Group Environment Questionnaire (Carron et al. 1985) and the Sociometry. The data were collected individually at the training. Descriptive statistics (mean and percent), Man-Whitney test for means difference and sociogramas were used for the data analyses and interpretation. Trough the results was verified: The individual task attraction to the group showed 16 points and the group task integration 17,4 points; the individual social attraction to the obtained 20,6 points and social integration 18,8. The titular team showed higher levels for the group social integration and for the individual attraction to the group (task and social) than the reserve team. But the reserve team showed higher levels for the group task integration. The data demonstrated that the group showed deficiency in the matter of cohesion, for both social and task cohesion; however, in spite of the indicators for lack of group cohesion, the athletes demonstrated preference to play with those who possessed better technical performance. So it is concluded: cohesion represents an essential element for a high performance team, showing the influence of grou integration-social and group integration-task.
Keywords: Sport cohesion; social relations; motor performance